Sexually Transmissible Diseases - psychosocial analysis of deaf studentsâ representations - JanaÃna Francisca Pinto Fernades (2008)
This study approaches deaf peopleâs social representations in the concerning to sexually transmissible diseases, due to the difficulty deafness causes in communication and, consequently, in the acquisition of contents on STD, strengthening susceptibility to such diseases. The research was carried out in a basic education deaf school. It aimed at: learning deaf studentsâ social representations on STD; identifying representations related to information acquirement, ways of STD contamination and prevention; interpreting their own social representations face to others and to themselves. The exploratory study was carried out with stratified sample with students from 6th to 9th grades studying in the three times. To data collection, the researcher used the Word Association Test (WAT), the draw-a-story theme based test survey and reports in field diary. Population consisted of 174 students and the sample of 107. Statiscal Package for Science Program, version 13.0 organized qualitative WAT and survey data. WAT data interpretation was proceeded with correspondence analysis and survey data with content correspondence. Results show that about 50% are male or female, with average age of 21. A little more than a half of them report knowing STD topic, and two are the ways of acquiring such information: alone, through books and magazines, and through other people (friends, neighbors etc) followed by school. Family members reported as responsible for information students highlighted mother, and mother and father together. AIDS is the most known disease, followed by hepatitis B and syphilis. Furthermore, they believe that diseases like dengue, leishmaniasis and yellow fever, that are transmitted by insect bite, are also sexually transmissible. Related to contamination, they have reported genital, oral and anal sex, as well as syringe sharing with drugs use; a significant number of students reported sneezing and cough, mouth kiss and sharing cutlery can improve the risk for STD, because they involve spittle. The primary preventive method students report is condom, and they believe that using condoms is being hygienic. They show to believe that STD have a strong semantic relationship with sex, condom, penis, disease and AIDS, while STD itself is represented by the words/expressions: I donât, condom, cannot date, disease, sick, weak, penis, vagina, mouth (the three latter as both organs from body and sick organs). The expression âI donâtâ shows STD deny for themselves, so it is the otherâs sickness. The study is an evidence for the knowledge that deaf students realize STD in couples and sexual organs, that is, the very sexual act.